Multicultural Education as a Strategy for Strengthening Students’ Tolerance Attitudes in Islamic Boarding Schools in Lombok - Abdurrohman; Muh. Jaelani Al Pansori; Lia Rismawati (KASTA : Jurnal Ilmu Sosial, Agama, Budaya dan Terapan, 2025)
Lombok is a region characterized by cultural, ethnic, and social diversity, which necessitates the implementation of multicultural values in education. Islamic boarding schools (pondok pesantren) play a strategic role as religious-based educational institutions in fostering tolerance among students. This study aims to describe the implementation of multicultural education in Islamic boarding schools in Lombok and its contribution to the development of students’ tolerance attitudes. This research employed a qualitative approach using a descriptive method. Data were collected through observations, in-depth interviews with pesantren leaders, teachers, and students, as well as document analysis of learning activities and pesantren culture. The findings indicate that multicultural education in Lombok’s Islamic boarding schools is implemented through the integration of tolerance values in classroom learning, educators’ role modeling, religious and social activities, and daily habituation of living together in a diverse pesantren environment. These practices contribute to the development of mutual respect, openness, and acceptance of differences among students. The study concludes that Islamic boarding schools have significant potential as strategic spaces for the development of multicultural education oriented toward strengthening students’ tolerance attitudes.